Oral Sciences PhD Program Enrollment, Graduates, and Placement: 1994 to 2016. - Herzog, C. R.; Berzins, D. W.; DenBesten, P.; Gregory, R. L.; Hargreaves, K. M.; Messer, R. L. W.; Mina, M.; Mooney, M. P.; Paine, M. L.; Phillips, C.; Presland, R. B.; Quivey, R. G.; et al. (Journal of Dental Research, 2018)
For decades, dental schools in the United States have endured a significant faculty shortage. Studies have determined that the top 2 sources of dental faculty are advanced education programs and private practice. Those who have completed both DDS and PhD training are considered prime candidates for dental faculty positions. However, there is no national database to track those trainees and no evidence to indicate that they entered academia upon graduation. The objective of this study was to assess outcomes of dental school-affiliated oral sciences PhD program enrollment, graduates, and placement between 1994 and 2016. Using the American Dental Association annual survey of advanced dental education programs not accredited by the Commission on Dental Accreditation and data obtained from 22 oral sciences PhD programs, we assessed student demographics, enrollment, graduation, and placement. Based on the data provided by program directors, the average new enrollment was 33, and graduation was 26 per year. A total of 605 graduated; 39 did not complete; and 168 were still in training. Among those 605 graduates, 211 were faculty in U.S. academic institutions, and 77 were faculty in foreign institutions. Given that vacant budgeted full-time faculty positions averaged 257 per year during this period, graduates from those oral sciences PhD programs who entered academia in the United States would have filled 9 (3.6%) vacant faculty positions per year. Therefore, PhD programs have consistently generated only a small pipeline of dental school faculty. Better mentoring to retain talent in academia is necessary. Stronger support and creative funding plans are essential to sustain the PhD program. Furthermore, the oral sciences PhD program database should be established and maintained by dental professional organizations to allow assessments of training models, trends of enrollment, graduation, and placement outcomes.